Epigenetic Sensitisation of Chemotherapeutic Compounds in Non- Small Cell Lung Cancer - Alnefaie, Ghaliah Obaid F. (Epigenetic Sensitisation of Chemotherapeutic Compounds in Non- Small Cell Lung Cancer, 2021)
Lung cancer is currently the highest cancer-related cause of death worldwide, accounting for 1.7 million deaths in 2018. Non-small cell carcinoma (NSCLC) is the most frequent type, accounting for approximately 80% of all lung cancer cases. Chemotherapy is still the first-line therapy offered to NSCLC patients in most countries. While new therapies (targeted compounds, immunotherapy) are evolving, chemotherapy is considered to be used for at least two more decades. Resistance to chemotherapy is among the major factors contributing to lung cancer mortality and has been well established to date through multiple preclinical studies and clinical trials. Currently, there are very few biomarkers, mostly clinical, for predicting chemotherapy efficiency. In addition, sensitization of cancer cells to those compounds is largely ineffective clinically. This study explores new avenues of lung cancer cell sensitization to four common chemotherapeutics (cisplatin, carboplatin, gemcitabine, and vinorelbine), with a particular focus in epigenetics and the role of extracellular vesicles. Using a wide spectrum of molecular and cell biology methods (cloning, inducible transgene expression, shRNA-based silencing, proliferation and apoptosis assays, the neutral comet assay, RT-qPCR, pyrosequencing-based DNA methylation analysis, western blots, EV isolation and characterisation etc.), I analysed a large number of parameters in relation to drug resistance in NSCLC cell lines. Following establishment of the IC50 of each four drugs in eight NSCLC cell lines, resistant cell lines were chosen for sensitization with epigenetic drugs (VPA and DAC), Aminomethylphosphonic acid (AMPA) and fendiline. VPA demonstrated a significant sensitization potential for all the four chemotherapeutics and this is a novel finding for lung cancer cells. Both VPA and DAC triggered a significant increase in apoptosis activity in cells treated with cisplatin or carboplatin. Double strand DNA breaks were caused by gemcitabine in A549, CALU-6 and COR-L23 the NSCLC cell lines and pre- treatment with VPA increased this effect, this also being a novel finding in this study. I also looked into the role of LANCL1-AS1; a long-noncoding RNA, which our research group found to be diminished in NSCLC tissues. After establishing an inducible expression model in the SK-MES-1 cell line, it was shown, contrary to the original hypothesis, that LANCL1-AS1 triggered an increase in proliferation rate, migration invasion, sensitivity to gemcitabine and vinorelbine, increased resistance to platin compounds and, interestingly, expression of its coding counterpart gene, LANCL1. LANCL1 shRNA-based silencing led to a decrease in proliferation, migration and sensitivity to oxidative stress. However, sensitivity to all four drugs followed the same pattern as for overexpression of LANCL1-AS1, raising thus questions on whether these two functions are related or independent, without being able at this point to exclude the off-target effects of the shRNA approach. Relatively recently, the role of extracellular vesicles (EVs)' in cancer development and drug resistance has come under investigation. I thus decided to test whether the LANCL1-AS1 dependent sensitivity to gemcitabine can be transferred through EVs. Increased LANCL1-AS1 expression led to an increase in the EVs release in a dose-dependent manner. Unfortunately, a number of technical issues related to the toxicity of the EV isolation reagent did not allow establishing knowledge of how LANCL1-AS1 induced EVs affect gemcitabine resistance when transferred to a recipient cell line. In conclusion, this study has provided a number of novel insights into sensitizing NSCLC cells in a preclinical setting. Further research is required to establish whether these results have clinical value and how they might affect clinical management of lung cancer.